Packaging of Post Acclimatized Somatic Embryogenesis Cocoa Plantlet (Theobroma cacao L.) - Soedarsianto Soedarsianto; Teguh Iman Santoso (Indonesian Coffee and Cocoa Research Institute, 2009)
Clonal plants that produced by somatic embryogenesis technique is one of the best choice to produce supperior clonal cacao (Theobroma cacao L.) planting materials. The somatic embryogenesis technique is a possible way for massive propagation, the outcome is true to type plants, the architecture similarity that the seedlings but there is not segregation like seedlings plants. At present mass production started of plantlets production until post-acclimatized plantlets of somatic embryogenesis cocoa was done at Indonesian Coffee and Cocoa Research Institute. Distribution system of the planting materials to whole areas in form of as up-rooted post-acclimatized plantlet. Some problems identified to reduce probability of decreasing viability of up-rooted post-acclimatized plantlets and one of them is extreme internal water deficit. This research investigate of the influece storage condition (air tight and non-air tight) and box storage (mica plastic and cardboardbox). The first experiment result show, there is no significant different between mica plastic and cardboard box usage for storage of post-acclimatized cocoa pantlet. Viability of up-rooted post acclimatized cocoa plantlet influenced exactly by air tight and non-air tight storage condition. Air tight storage condition have better viability of up-rooted post acclimatised (81,58%) than non-air tight storage condition (65,00%). Leaf sanasence on air tight storage condition (10,33%) lower than non-air tight storage (32,58%). There is not significantly on volume storage per plantlet between 4.416 cm3 and 12.600 cm3. Relationship between fallen leaves and cocoa planlet viability follow negative linear correlation y = -1,4719x + 104,88 (R2 = 0,9772). The second experiment treatment showed that maximal storage periode of post cclimatized cocoa plantlet just until 6 days stored (97%) and not significant with 3 days one. Viability of post acclimatized cocoa plantlet decreased after 6 days storage period.Key words : Somatic embryogenesis, post acclimatized cacao plantlet, storage condition, box storage, volume storage, storage period and viability.